Վազգեն Ա Հայրապետի գործունեությունը Ռումինիայում - Լիլիթ Պողոսյան (ՀՀ ԳԱԱ հրատ.)
The article focuses on the midcatholicosian activity carried out by Bishop Vazgen Palchyan in Romania during World War Second. There is also a small narration about the life and activity of Catholicos’s parents. The article also brings citations from the book by A. Mnatcakanyan, where it is told how the future catholicos could safe and pass to our generetions works by Mnatcakanyan when he was a hostage and was given a visit by the future Catholicos in Romania.
Keywords: Armenian Diaspora; Philosophy; Psychology; Religion; Religion; Biography; Modern History